Implementasi Sistem Pakar Dengan Metode Certainty Factor Dan Forward Chaining Pada Helpdesk UPT TIK Unsika - Muhammad Fahmi Prasetio; Apriade Voutama; Garno Garno (Jurnal Ilmiah Wahana Pendidikan, 2022)
UPT TIK as one of the service units at Singaperbangsa KarawangUniversity which helps overcome problems related to the use ofinformation facilities within the Singaperbangsa Karawang University.One of the efforts made by UPT TIK to improve services is by providingHelpdesk services. Over time this Helpdesk still has a weakness, when thenumber of problems is very large but the number of technicians availableis very limited and all problems must be solved with the possibility of notdisturbing activities on the campus of Singaperbangsa KarawangUniversity. Therefore, it is necessary to optimize services so that they areable to serve without the help of a technician who is an expert in their fieldto deal with existing problems. An expert system is a use of artificialintelligence technology to support every activity. This study aims to applythe system to the existing Helpdesk service with Certainty Factor reasoningand Forward Chaining methods. At the development stage, this systemuses the ESDLC (Expert System Development Life Cycle) method whichconsists of knowledge, conceptualization, formalization, implementation,and testing. The results obtained in the study were as many as 13 rules thatwere implemented in the UPT TIK Helpdesk service at SingaperbangsaKarawang University with an accuracy rate of 90%.